Effect of fatigue upon performance and electromyographic activity in 6-RM bench press - van den Tillaar, R.; Saeterbakken, A. (Journal of Human Kinetics, 2014)
The aim of this study was to examine the effect of fatigue during one set of 6-RM bench pressing upon the muscle patterning and performance. Fourteen resistance-trained males (age 22.5±2.0 years, stature 1.82±0.07 m, body mass 82.0±7.8 kg) conducted a 6-RM bench press protocol. Barbell kinematics and EMG activity of pectoralis major, deltoid anterior, biceps brachii, triceps brachii, rectus abdominis, oblique external and erector spinae were measured in each repetition during the 6-RM bench press. Total lifting time increased and the velocity in the ascending movement decreased (p=0.001). However, the kinematics in the descending phase deferred: the time decreased and velocity increased during the 6-RM (p=0.001). Generally, muscles increased their EMG amplitude during the six repetitions in the ascending movement, while only three of the seven measured muscles showed an increase over the six repetitions in the descending part in 6-RM bench pressing. It was concluded that the bench pressing performance decreased (lower barbell velocities and longer lifting times) with increasing fatigue in the 6-RM execution. Furthermore EMG increased in the prime movers and the trunk stabilizers (abdominal and spine), while the antagonist muscle (biceps) activity was not affected by fatigue during the lifting phase in a single set of 6-RM bench pressing.